Lyme : the first epidemic of climate change - Pfeiffer, Mary Beth (Island Press, 2018)
Lyme disease is spreading rapidly around the globe as ticks move into places they could not survive before. The first epidemic to emerge in the age of climate change, Lyme infects half a million people in the US and Europe each year, and untold multitudes in Canada, China, Russia, and Australia. Mary Beth Pfeiffer traces how we have contributed to this growing menace, and how modern medicine has underestimated its danger. She tells the stories of families devastated by a single tick bite, of children denied care, and of one women's wrenching choice after a fruitless search for a cure. Pfeiffer also warns of the emergence of other tick-borne illnesses that make Lyme more difficult to treat and pose their own grave risks. Lyme is an impeccably researched account of an enigmatic disease, making a powerful case for action to fight ticks, heal patients, and recognize humanity's role in a modern scourge.--Dust jacket.